2017
DOI: 10.3390/languages2040020
|View full text |Cite
|
Sign up to set email alerts
|

Determiner Asymmetry in Mixed Nominal Constructions: The Role of Grammatical Factors in Data from Miami and Nicaragua

Abstract: This paper focuses on the factors influencing the language of determiners in nominal constructions in two sets of bilingual data: Spanish/English from Miami and Spanish/English creole from Nicaragua. Previous studies (Liceras et al. 2008;Moro Quintanilla 2014) have argued that Spanish determiners are preferred in mixed nominal constructions because of their grammaticised nature. However, those studies did not take the matrix language into account, even though Herring et al. (2010) found that the language of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 22 publications
2
70
1
Order By: Relevance
“…For example, the Matrix Language framework (Myers-Scotton 2002) proposes an asymmetric relationship between the two constituent languages such that one language provides the morphosyntactic frame (i.e., the matrix language) and the other primarily contributes content elements. This account finds empirical support in the language selection of determiners in mixed NPs, which correspond to the matrix language of the clause (Blokzijl et al 2017;Herring et al 2010; Parafita Couto and Gullberg 2017). On the other hand, generative accounts suggest that Spanish determiners should be preferred due to the overt grammatical checking features necessary for Spanish gender assignment and agreement (e.g., Liceras et al 2008Liceras et al , 2016.…”
Section: Accounting For Codeswitching Distributionsmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, the Matrix Language framework (Myers-Scotton 2002) proposes an asymmetric relationship between the two constituent languages such that one language provides the morphosyntactic frame (i.e., the matrix language) and the other primarily contributes content elements. This account finds empirical support in the language selection of determiners in mixed NPs, which correspond to the matrix language of the clause (Blokzijl et al 2017;Herring et al 2010; Parafita Couto and Gullberg 2017). On the other hand, generative accounts suggest that Spanish determiners should be preferred due to the overt grammatical checking features necessary for Spanish gender assignment and agreement (e.g., Liceras et al 2008Liceras et al , 2016.…”
Section: Accounting For Codeswitching Distributionsmentioning
confidence: 86%
“…"Codeswitching sites" refer to syntactic constituents at which bilingual speakers appear to systematically switch from one language to another. Codeswitching preferences conform to community-based norms, and are therefore not necessarily generalizable across bilingual populations, even within the same language pair (Blokzijl et al 2017;Poplack 1988). Identification of distributional patterns is achieved by the quantification and extraction of codeswitching sites from recordings of naturalistic language (Poplack 1980;Torres Cacoullos and Travis 2015).…”
Section: Corpus-based Analysis Of Codeswitchingmentioning
confidence: 99%
“…Blokzijl, Deuchar & Parafita Couto (2017) has recently suggested that switches tend to be towards the language of power or the language with superior social status. The patterns observed in the three corpora with Dets from what could be described as the minority languages (Welsh in the UK; Spanish in Miami; Papiamento in the Netherlands) and lexical material from 'majority' languages (English in the UK and in Miami; Dutch in the Netherlands) are certainly consistent with this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, borrowings in the opposite direction are not found, despite the students' extreme language limitations in Spanish vocabulary. The direction of borrowing points to the higher status and prestige of Spanish (Blokzijl et al 2017;Haspelmath 2009). Even when P'urhepecha is prioritised, monolingual preferences are evident in the separation of languages in school policy and classroom practice.…”
Section: Developing Biliteracy: Observations Across Languages and Conmentioning
confidence: 99%